Vitamin D levels in epileptic children on long-term anticonvulsant therapy - Fathy Pohan; Aryono Hendarto; Irawan Mangunatmadja; Hartono Gunardi (Indonesian Pediatric Society Publishing House, 2015)
Background Long-term anticonvulsant therapy, especially with enzyme inducers, has been associated with low 25-hydroxyvitamin D [25(OH)D] levels and high prevalence of vitamin D deficiency. However, there have been inconsistent results in studies on the effect of long-term, non-enzyme inducer anticonvulsant use on vitamin D levels. Objective To compare 25(OH)D levels in epileptic children on long-term anticonvulsant therapy and non-epileptic children. We also assessed for factors potentially associated with vitamin D deficiency/insufficiency in epileptic children. Methods This cross-sectional study was conducted at two pediatric neurology outpatient clinics in Jakarta, from March to June 2013. Subjects in the case group were epileptic children, aged 6-11 years who had used valproic acid, carbamazepine, phenobarbital, phenytoin, or oxcarbazepine, as a single or combination therapy, for at least 1 year. Control subjects were non-epileptic, had not consumed anticonvulsants, and were matched for age and gender to the case group. All subjects' 25(OH)D levels were measured by enzyme immunoassay. Results There were 31 epileptic children and 31 non-epileptic control children. Their mean age was 9.1 (SD 1.8) years. Most subjects in the case group were treated with valproic acid (25/31), administered as a monotherapy (21/31). The mean duration of anticonvulsant consumption was 41.9 (SD 20) months. The mean 25(OH)D level of the epileptic group was 41.1 (SD 16) ng/mL, lower than the control group with a mean difference of 9.7 (95%CI 1.6 to 17.9) ng/mL. No vitamin D deficiency was found in this study. The prevalence of vitamin D insufficiency in the epileptic group was higher than in the control group (12/31 vs. 4/31; P=0.020). No identified risk factors were associated with low 25(OH)D levels in epileptic children. Conclusion Vitamin D levels in epileptic children with long-term anticonvulsant therapy are lower than that of non-epileptic children, but none had vitamin D deficiency.